The Form and Use of Swearing Words in the Movie the Wolf of the Wall Street - Mahadiputra, I Gusti Ngurah (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p20, 2018)
This paper is entitled “The Form and the Use of Swearing Words in the Wolf of the Wall Street Movie”. This study aims to identify the kinds of swearing words and explain the purpose of the use of swearing words in the movie. The data were collected directly from the movie subtitle as the data source. The data of swearing words were collected by note-taking technique, the dialogues containing swearing words were noted and then the best ones were chosen to be analyzed according to the theory. The data were analyzed by using the qualitative method, and analyzed based on the theory of classification of swearing words proposed by Hughes (1991) to identify the kinds of swearing words and theory of principle purpose of verbal obscenity proposed by Liedlich (1972) used to analyze the purpose of the use of swearing words. The finding shows that there are six kinds of swearing words found. The kinds of swearing words found in the movie are indicated from the genital term, excretory term, animal term, anatomical term, imbecilic term, and general term. All those words are used in the informal situation and mostly used by the character to express their feeling such as anger, happiness and their dissatisfaction with something. Besides, from seven principal purposes of verbal obscenity, there are six purposes of using swearing words found in this study; they are swearing words used to provide catharsis, to discredit, the term of endearment, to show personal identification, to create attention, and to insult. By using swearing words they can express their emotion and feel as well. Generally, swearing words are not allowed to be spoken in daily conversation but in this movie, all characters mostly used swearing words in their daily conversations.